2001
DOI: 10.1016/s0022-2275(20)31677-1
|View full text |Cite
|
Sign up to set email alerts
|

Induction of acyl-coenzyme A:cholesterol acyltransferase-1 by 1,25-dihydroxyvitamin D3 or 9-cis-retinoic acid in undifferentiated THP-1 cells

Abstract: We have previously shown that acyl-coenzyme A: cholesterol acyltransferase-1 (ACAT-1) protein content increases significantly during the human monocyte-macrophage differentiation process. To gain further insight, we used undifferentiated human monocytic THP-1 cells as a model system with which to examine whether ACAT-1 mRNA and protein content can be increased by treating cells with 1,25-dihydroxyvitamin D 3 [1,25-(OH) 2 D 3 ] or with 9-cis -retinoic acid (9-cis -RA), two agents known to upregulate the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Changes in ACAT1 mRNA expression, either by differentiation of THP1 cells into macrophages or OA, AA, or EPA incubation in HepG2 cells, were observed only in the major 3.8 and 4.3 kb bands. Similarly, only these two transcripts are modulated in THP1 cells by vitamin D 3 or 9-cis-retinoic acid (11). Presumably, FFAs might only affect transcription from sequences proximal to ACAT1 gene (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in ACAT1 mRNA expression, either by differentiation of THP1 cells into macrophages or OA, AA, or EPA incubation in HepG2 cells, were observed only in the major 3.8 and 4.3 kb bands. Similarly, only these two transcripts are modulated in THP1 cells by vitamin D 3 or 9-cis-retinoic acid (11). Presumably, FFAs might only affect transcription from sequences proximal to ACAT1 gene (9).…”
Section: Discussionmentioning
confidence: 99%
“…[1,2-3 H(N)]Cholesterol, [4- 14 C]cholesterol, [9,10-3 H(N)]oleic acid, and [R-32 P]deoxycytidine 5′-triphosphate (3000 Ci/mmol) were purchased from Dupont NEM, Wilmington, DE. [5,6,8,9,11,12,14,15,17, Cells. HepG2 human hepatocytes (15) and THP1 human monocyte/macrophages were grown as described previously (16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding implicates that once the inhibitor binds to the ACAT enzyme, it stays firmly bound for a few hours before dissociating from the enzyme. Based on this finding, we treated the animals with the inhibitor by IV injection, perfused the mice after the animals were treated (to remove blood contamination from the tissues), then prepared the tissue homogenates, and monitored the ACAT enzyme activity in these tissues by using the mixed micelles enzyme assay described previously [ 24 , 39 , 49 , 50 ] (the mixed micelles assay measures the ACAT enzyme activity independent of endogenous lipid composition because it reconstitutes the ACAT protein in mixed micelles with a defined lipid composition). We injected nanoparticles with F12511 (nanoparticle F) at 5.8 mg/kg or with K604 at 40 mg/kg by IV.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo, ACAT1 detected by immunohistochemical staining is abundantly present in lipid-rich atherosclerotic lesions (27). Additional cell culture work showed that in the human monocytic cell line THP-1, ACAT1 gene expression is upregulated by 1,25-dihydroxyvitamin D 3 (28). In human macrophages and macrophage-like cells, the ACAT1 gene is upregulated by the cytokine interferon ␥ (29).…”
mentioning
confidence: 99%